Sex Ecologies - Hessler, Stefanie (Trondheim ; Linköping ; Cambridge, Massachusetts : Kunsthall Trondheim : The Seed Box : The MIT Press, 2021)
Aglert,Katja ; Bates, Tarsch ; adrienne maree brown ; Chen, Mel Y. ; Doutreluingne, Pauline ; Eshraghi, Léuli ; Fan, Jes ; Fazlic, Ibrahim ; Halberstam, Jack ; niilas helander ; Hval, Jenny ; Hessler, Stefanie ; Jordan, Anne Duk Hee ; Kleemann, Jessie ; Lorde, Audre ; Lykke, Nina ; Madariaga-Caro, Montserrat ; Marambio, Camila ; Neimanis; Astrida ; Neves Marques, Pedro ; Okpokwasili, Okwui ; Pereira, Marie Helene ; Pettersen, Margrethe ; Prouvost, Laure ; Ramos, Filipa ; Sandilands, Catriona ; Schalk, Sami ; Serubiri Moses ; Simpson, Leanne Betasamosake ; Sprinkle, Annie ; Stephens, Beth ; TallBear, Kim ; Tje, Anna ; Whittle, Alberta ; Wibeck, Victoria ; Wilk, Elvia
Sex Ecologies explores pleasure, affect, and the powers of the erotic in the human and more-than-human worlds. Arguing for the positive and constructive role of sex in ecology and art practice, these texts and artistic research projects attempt nothing short of reclaiming the sexual from Western erotophobia and heteronormative narratives of nature and reproduction. The artists and writers set out to examine queer ecology through the lens of environmental humanities, investigating the fluid boundaries between bodies (both human and nonhuman), between binary conceptions of nature as separate from culture, and between disciplines. (provided by publisher)
"Sex Ecologies", Kunsthall Trondheim, Trondheim, December 9, 2021 - March 6, 2022
boek